2024
DOI: 10.3389/fmed.2024.1337367
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of torque teno virus load in kidney transplant recipients with indication biopsy and therapeutic modifications of immunosuppression

Marvin Reineke,
Christian Morath,
Claudius Speer
et al.

Abstract: Following kidney transplantation, lifelong immunosuppressive therapy is essential to prevent graft rejection. On the downside, immunosuppression increases the risk of severe infections, a major cause of death among kidney transplant recipients (KTRs). To improve post-transplant outcomes, adequate immunosuppressive therapy is therefore a challenging but vital aspect of clinical practice. Torque teno virus load (TTVL) was shown to reflect immune competence in KTRs, with low TTVL linked to an elevated risk for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…With a substantial proportion of kidney transplant recipients treated with CNI-free immunosuppressive regimen, it is necessary to further analyze the TTV load kinetic in these patient cohorts. 8 In Figure 1 , we illustrate a timeline of landmark studies that have shown the associations of TTV loads and kinetics with different immunosuppressants in SOT.
Figure 1 Type of immunosuppression and TTV.
…”
mentioning
confidence: 99%
“…With a substantial proportion of kidney transplant recipients treated with CNI-free immunosuppressive regimen, it is necessary to further analyze the TTV load kinetic in these patient cohorts. 8 In Figure 1 , we illustrate a timeline of landmark studies that have shown the associations of TTV loads and kinetics with different immunosuppressants in SOT.
Figure 1 Type of immunosuppression and TTV.
…”
mentioning
confidence: 99%